Building a Value-Oriented Digital Business Model for Traditional Anti-Migraine Herbal Tea Products - Renaldo, Nicholas; Veronica, Kristy; Panjaitan, Harry Patuan; Junaedi, Achmad Tavip; Fadrul, Fadrul; Andi, Andi; Suhardjo, Suhardjo; Susanti, Wilda; Tendra, Gusrio; Jahrizal, Jahrizal (Luxury: Landscape of Business Administration, 2025)
The growing demand for natural health solutions and the integration of digital lifestyles presents new opportunities for innovation in traditional herbal products. This study aims to design a value-oriented digital business model for an anti-migraine herbal tea, combining traditional herbal knowledge with modern digital entrepreneurship and accounting systems. The research used a qualitative approach, integrating the Business Model Canvas (BMC), Value Proposition Canvas (VPC), and digital accounting to formulate a scalable and consumer-centric business framework. The herbal formulation, consisting of ginger, peppermint, turmeric, lemongrass, lavender, cinnamon, and stevia, was developed based on scientific literature and traditional practices. Through consumer insights, market segmentation, and prototype evaluation with stakeholders and experts, the model was validated for its market viability and alignment with health-conscious and digital native consumers. The findings indicate that the integration of digital accounting enhances transparency, financial control, and business credibility, while the overall model supports sustainability, traceability, and value creation. This research contributes to the fields of digital business, sustainable product innovation, and the commercialization of traditional medicines. Future research is recommended to combine quantitative validation and clinical testing to improve the robustness and impact of the model.